Comprehensive Analysis of the Safety Profile of a Single-Stranded RNA Nano-Structure Adjuvant - Hyeong-Jun Park; Hae Li Ko; Dong-Hoon Won; Da-Bin Hwang; Yoo-Sub Shin; Hye-Won Kwak; Hye-Jung Kim; Jun-Won Yun; Jae-Hwan Nam (MDPI AG, 2019)
Adjuvants enhance the efficacy of vaccines by stimulating immune response-related gene expression and pathways. Although some adjuvants have been approved for commercial use in human vaccines (e.g., Alum, MF59, and AS03), they might elicit adverse side effects, such as autoimmune diseases. Recently, we developed a novel single-stranded RNA (ssRNA) nano-structure adjuvant, which can stimulate both Th1 and Th2 responses. In this study, we evaluated the safety and toxicological profiles of this ssRNA nano-structure adjuvant in vitro and in vivo. Mice were intramuscularly immunized with the ssRNA nano-structure adjuvant three times, once every 2 weeks. The results indicate no significant differences in hematological and serum biochemistry parameters between the ssRNA-treated groups and the control group. From a histopathological perspective, no evidence of tissue damage was found in any group. The levels of IgE and anti-nuclear antibodies, which are markers of autoimmune disease, were not different between the ssRNA-treated groups and the control group. The findings of this study suggest that the ssRNA nano-structure can be used as a safe adjuvant to increase vaccine efficacies.